EFFECT OF BEHAVIORAL PROBLEMS OF CHILDREN WITH AUTISM ON THEIR MOTHER’S QUALITY OF LIFE - Waheed, Ayesha; Khan, Mussarat Jabeen; Khurshid, Maryam (Pakistan Armed Forces Medical Journal, 2020)
Object: The aim of the present study was to assess effect of behavioral problems of children with Autism on their mother’s quality of life.Study Design: Cross-sectional study designPlace and Duration of Study: The sample was selected from different special education institutes of Islamabad and Rawalpindi. Duration of study was from March 2017 to September 2017.Participants and Methods: The Study was conducted on 100 participants (N=100, n= 50 mothers, n=50 diagnosed children with Autism). Convenient and snowball sampling technique was used to collect data. Two questionnaires were administered to assess Quality of life (WHO Quality of life scale -BREF) and behavior problems of children with Autism (Childhood Autism Rating Scale-CARS).Results: Results showed that quality of life of mothers has a significant negative relationship with their children’s autism related behavioral problems. Quality of life was found high in postgraduate mothers, while autism related behavioral problems were less in children with postgraduate mothers. Mothers living in joint family scored high on quality of, whereas child with Autism belonging to joint family system had fewer behavioral problems. Quality of life among working mothers was found high and children of working mothers exhibited less autism related behavioral problems than children of non-working mothers.Conclusion: Present study highlighted the importance of behavioral problems of children with Autism on their mother’s quality of life. The study would be helpful for the professionals for devising educational programs for mothers and treatment plans for their children with Autism.Keywords: Quality of life, Autism, behavioral problems